Association Between Glycaemic Control and Cardiac Function in Children with Diabetes Mellitus - M Ridho; Siska Mayasari Lubis; Putri Amelia; Juliandi Harahap; Rita Evalina; Fathia Meirina (GLOBAL HEALTH SCIENCE GROUP, 2025)
The prevalence of Diabetes Mellitus (DM) among children and adolescents has been progressively increasing, with Type 1 DM constituting the majority of cases. Cardiovascular disease (CVD) is a major long-term complication, yet early cardiac involvement remains poorly understood in this population. This study aimed to assess the association between glycaemic control and cardiac function in paediatric patients with DM. A cross-sectional observational study was conducted involving 30 children with type 1 or type 2 DM at H. Adam Malik General Hospital, Medan. Glycaemic control was assessed using HbA1c levels. Cardiac function was evaluated using electrocardiography (ECG) and echocardiographic parameters, including ejection fraction (EF), fractional shortening (FS), tricuspid annular plane systolic excursion (TAPSE), and E/A ratio. Data were analysed using Chi-Square and Mann-Withney Test. Most subjects (90%) had poor glycaemic control (HbA1c ≥7%). Cardiac dysfunction (reduced EF <55%) was identified in 16.7% of patients. However, no statistically significant associations were found between cardiac function and HbA1c, duration of diagnosis, blood pressure, or body mass index (BMI) (p>0.05). There was no significant relationship was found between glycaemic control and cardiac function, highlighting the need for more sensitive diagnostic tools and long-term follow-up to detect subclinical cardiovascular complications.